Integrating psychological reinforcement modalities to enhance the therapeutic efficacy of physical rehabilitation for disaster survivors - Dhiraj Kelly Sawlani; Yahdiana Harahap; Yuli Subiakto; Sutanto; Faonaso Harefa (Universitas Udayana dan Diaspora Taipei Medical University, 2026)
Background: Post-disaster physical rehabilitation programs in Sumatra have been running, but survivors still receive limited psychological support. Therefore, this study integrated spiritual guidance and light physical exercise to strengthen the psychological recovery process of disaster survivors. Methods: This study applied a mixed-method approach with an exploratory design where qualitative analysis utilizes NVivo 12 to examine data sourced from online media and interviews with 15 participants representing the Regional Government and psychology experts, while quantitative analysis used the structural equation modeling partial least squares – 4 (SEM PLS-4) on data collected from 150 health workers of Universitas Pertahanan, Indonesia who served in disaster-affected areas with a structured questionnaire as a research instrument. Results: The results of the NVivo 12 analysis identified stress, loss, uncertainty about the future, and various health problems, such as respiratory infections, diarrhea, skin diseases, and a high need for emotional support became important factors for implementing psychological recovery interventions. Based on the results of the SEM PLS-4 analysis, this finding was strengthened by showing that the integration of spiritual methods, psychosocial approaches, light physical activity, and fulfillment of basic needs had a positive and significant impact on psychological strengthening and recovery (β = 0.529; p = 0.000; T = 8.651; R² = 0.280; F² = 0.389). Furthermore, the developed model showed strong predictive capacity, as indicated by the Q²predict value of 0.267, with a lower PLS loss than the indicator average (IA) loss (0.149 < 0.204). Conclusion: Light physical activity, spiritual guidance, psychosocial support, and provision of basic needs were crucial factors in strengthening and restoring the psychological well-being of disaster survivors. Implementing holistic interventions in evacuation centers and at home has been shown to reduce stress levels, aid emotional regulation, restore physical function, and strengthen long-term mental resilience.